Knowledge, Attitude and Practice of Partner’s Presence in OT for Elective C-Section: A Caribbean Perspective - Ventour, Dale; Gardiner, Kadija (British Journal of Healthcare and Medical Research, 2023)
Objective: It is current practice in our setting to not admit a partner in the Caesarean room even though this is becoming commonplace in various countries. This study is designed to determine the views of healthcare workers, postpartum mothers and their accompanying partners on having a partner present during an elective Caesarean section at Port of Spain General Hospital, Trinidad, West Indies. Design: 94 participants were selected, a questionnaire was given to healthcare workers, patients and partners in November/ December 2021 to investigate the viewpoint of anaesthetists, obstetricians, midwives, operating room nurses, pregnant/post-partum mothers and their accompanying partners. Results: 70% of respondents were in favour of a partner being present in the operating room for an elective Caesarean section and thought it would help to keep the mother at ease by allowing her to hold hands with the partner, talk to them and be accompanied by them to the recovery room. Healthcare workers did not think that male partners had a role to play in the operating room as they would not know what to do and may actually pose a security threat if the operation did not go exactly as planned. Conclusions: Healthcare workers were neutral to the concept of a partner being present in the Caesarean room, while mothers and partners supported the idea. Future studies are needed to confirm if these observations are comparable among other public hospitals in other territories in the developing world where partner accompaniment is not a priority to mothers.